2009
DOI: 10.1002/pen.21398
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonation of solid polystyrene using gaseous sulfur trioxide

Abstract: Kinetics of the heterogeneous sulfonation of polystyrene (PS) beads using gaseous SO3 was investigated. Scanning electron microscopy (SEM) and electron diffraction scattering spectroscopy (EDS) was employed to study the kinetics of diffusion of SO3 into the PS particles. The diffusion of SO3 through the barrier of sulfonated polystyrene (SPS) on the beads surface was the primary parameter determining the rate and the yield of the sulfonation reaction. The measurement of the time dependence of the thickness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
52
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 19 publications
1
52
0
2
Order By: Relevance
“…A escolha das condições para sulfonação é feita considerando 3 fatores: nível de sulfonação, tipo de isômero formado e rendimento da reação. 8 O método mais freqüentemente empregado em meio homogêneo é a sulfonação do PS solubilizado em dicloroetano e o emprego do acetilsulfato, produzido pela reação do anidrido acético com o ácido sulfúrico concentrado, como agente sulfonante. 8 Poliestireno sulfonado com um elevado grau de sulfonação também pode ser obtido através da rota heterogênea.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…A escolha das condições para sulfonação é feita considerando 3 fatores: nível de sulfonação, tipo de isômero formado e rendimento da reação. 8 O método mais freqüentemente empregado em meio homogêneo é a sulfonação do PS solubilizado em dicloroetano e o emprego do acetilsulfato, produzido pela reação do anidrido acético com o ácido sulfúrico concentrado, como agente sulfonante. 8 Poliestireno sulfonado com um elevado grau de sulfonação também pode ser obtido através da rota heterogênea.…”
Section: Introductionunclassified
“…8 O método mais freqüentemente empregado em meio homogêneo é a sulfonação do PS solubilizado em dicloroetano e o emprego do acetilsulfato, produzido pela reação do anidrido acético com o ácido sulfúrico concentrado, como agente sulfonante. 8 Poliestireno sulfonado com um elevado grau de sulfonação também pode ser obtido através da rota heterogênea. Neste caso, pode-se empregar o PS em pó adicionado em ácido sulfúrico concentrado (agente sulfonante) e sulfato de prata como catalisador.…”
Section: Introductionunclassified
“…The sulfonation with chlorosulfuric acid can also create an acid disposal problem due to the generation of hydrogen chloride during the reaction process. 8 SO 3 as the sulfonating agent has some distinctive advantages compared with other sulfonating agents, such as high activity, fast reaction rate, high atom economy due to direct addition of SO 3 group, low material cost and minimal waste acid generation. Thus, SO 3 sulfonation is a clean and efficient process and has been extensively performed in chemical industry.…”
Section: Introductionmentioning
confidence: 99%
“…The mass and heat transfer coefficients in microreactors are larger than those in conventional reactors by two orders of magnitude. 19,20 The sulfonation of toluene with a gas mixture of SO 3 and N 2 as the sulfonating agent has been investigated in a microreactor system by Mü ller and his co-workers. 21 They found that high selectivity was obtained with precise temperature control and high pressure resistance of the microreactor at a SO 3 : toluene molar ratio of 0.05-0.15.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation